Understanding early contextual and parental risk factors for the development of limited prosocial emotions - Waller, Rebecca (J Abnorm Child Psychol, 2015)
A growing body of evidence suggests that parenting influences the development of youth callous unemotional (CU) behavior. However, less is known about the effects of parenting or contextual risk factors on ‘limited prosocial emotions’ (LPE), a recent conceptualization of CU behavior added to the DSM-5. We focused on LPE at ages 10–12 and age 20 among low income, urban males (N = 310), and examined potential developmental precursors, including contextual risk factors assessed during infancy and observed maternal warmth during the toddler period. We found unique direct associations between maternal warmth, maternal aggression, and low empathetic awareness on LPE at ages 10–12, controlling for concurrent self-reported antisocial behavior. Further, there were indirect effects of maternal aggression, low empathetic awareness, and difficult infant temperament assessed in infancy on LPE at ages 10–12 via their influence on maternal warmth at age 2. Finally, there were lasting indirect effects of parental warmth on LPE at age 20, via LPE at ages 10–12. We discuss the implications of these findings for ecological models of antisocial behavior and LPE development, and preventative interventions that target the broader early parenting environment.